Etiological spectrum and short term outcome of acute kidney injury in children: a prospective study - Mahesh, K.; B., Vishwanath; S., Kalpana (International Journal of Contemporary Pediatrics, 2019)
Background: Acute Kidney Injury is a common condition in critically ill children, and it is independently associated with increased mortality. Etiology of AKI in admitted patients is multi factorial. The present study was conducted to determine possible etiologies and to know short term outcome. Methods: A prospective case series study was conducted in our PICU from Nov 2014 to October 2015. The cases fulfilling criteria as AKI, as per definition were included in study. The urine output was monitored, base line blood urea and serum creatinine was estimated at admission and on alternate days till recovery. Investigations were done to know exact etiology of prerenal, renal or post renal AKI. Cases were managed accordingly and short term outcome was noted. Results: Out of 150 cases studied, 87(58%) were boys and 63(42%) were girls. Ninety three cases (62%) had oliguria and remaining patients had non-oliguric AKI. Majority of cases in the study belonged to prerenal AKI, followed by renal and post renal AKI. Amongst 150 cases,136 children managed conservatively,11 cases required hemodialysis and 3 cases peritoneal dialysis. In our study, 16 cases succumbed with mortality of 10.66%. Conclusion: AKI is common associated condition in children admitted to PICU. AKI is commonly seen with acute gastroenteritis with severe dehydration, sepsis, glomerulonephritis and dengue shock syndrome. Most of these conditions are easily preventable. Early and effective management of hypovolemic shock and sepsis is also crucial in prevention of AKI.